Effect of raw material on cooking quality and nutritional composition of durum wheat spaghetti. (May 2015) - Padalino, L.; Mastromatteo, M.; Lecce, L.; Spinelli, S.; Conte, A.; Del Nobile, M. A.
Abstract In this study the effect of semolina and wholemeal flour from six durum wheat cultivars on the pasta cooking and nutritional quality was evaluated. The wholemeal spaghetti samples showed an improvement in the chemical composition (high protein and insoluble dietary fibre content) but they have a decline in the cooking quality (high cooking loss) with respect to the semolina spaghetti. In particular, the wholemeal spaghetti Cappelli and Core samples recorded the highest protein and insoluble dietary fibre content, respectively. As compared to the other samples, the wholemeal spaghetti Iride recorded a higher cooking loss. Moreover, the wholemeal spaghetti showed the lowest overall quality due to the low score of elasticity, firmness and colour. Specifically, the wholemeal Cappelli recorded a slight rise of the overall quality with respect to other wholemeal samples. In conclusion, the wholemeal spaghetti Cappelli was found to be an optimum compromise between the sensory and nutritional quality.